The Effect of Peer Support Group on Depression and Quality of Life among People Living with HIV/AIDS in Kediri East Java - Astika Rasyiid; Ruben Dharmawan; Supriyadi Hari Respati (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: People living with Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome or HIV/AIDs encounter such problems as society stigma and depression that can affect their quality of life in the term of physical, mental, and social health. Social support should be improved from individual, family, Peer Support Group (PSG), and government. PSG serves to help PLWHA feel not lonely, to give opportunity of seeing others, of sharing information about newest treatment and local support service, to reduce isolation, to improve social support, and to reduce stigma in order to achieve better quality of life and to reduce depression. The objective of research was to analyze the effect of KDS on depression and quality of life among PLWHA in Friendship Plus Peer Support Group in Kediri City.Subjects and Method: This study was an analytical observational study with cross sectional design. This was conducted at Friendship Plus Peer Support Group in Kediri, Indonesia in May to July 2016. The sample consisted of 60 subjects taken using simple random sampling. Technique of collecting data used was questionnaire, while analysis was carried out using Pearson’s Product Moment correlational and multiple linear regression tests.Results: The result of research showed that there was a statistically significant effect of Peer Support Group on the reduced depression in PLWHA (b= -0.60; 95% CI= -0.82 to 0.38; p<0.001). Depression was affected by family income of 88.8% (b= -8.68; 95% CI= 0.01; p=0.021) and education (b= -7.86; 95% CI= -14.05 to 1.67; p=0.014). There was a statistically significant effect of Peer Support Group on the improved quality of life among PLWHA (b=0.32; 95% CI= 0.09 to 0.53; p=0.005). Quality of life was affected by family income of 92.3% (b= 1.36; 95% CI= 0.01; p<0.001) and education (b=20.84; 95% CI= 14.75 to 26.93; p<0.001). Conclusion: This research concluded that there was an effect of peer support group on the reduced depression among PLWHA and there was an effect of peer support group the improved quality of life among PLWHA.Keywords: peer support group, depression, quality of life, PLWHACorrespondence: Astika Rasyiid. Diploma III Midwifery of Tulungagung University, East Java.Journal of Health Promotion and Behavior (2016), 1(1): 32-40https://doi.org/10.26911/thejhpb.2016.01.01.05